2017
DOI: 10.1093/pasj/psx121
|View full text |Cite
|
Sign up to set email alerts
|

Kilonova from post-merger ejecta as an optical and near-Infrared counterpart of GW170817

Abstract: Recent detection of gravitational waves from a neutron star (NS) merger event GW170817 and identification of an electromagnetic counterpart provide a unique opportunity to study the physical processes in NS mergers. To derive properties of ejected material from the NS merger, we perform radiative transfer simulations of kilonova, optical and near-infrared emissions powered by radioactive decays of r-process nuclei synthesized in the merger. We find that the observed near-infrared emission lasting for > 10 days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
189
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(211 citation statements)
references
References 50 publications
21
189
0
1
Order By: Relevance
“…A fit of AT2017gfo light curves to a semianalytical two-components spherical model indicates a lanthanide poor (rich) blue (red) component of mass 2.5×10 −2 M (5.0×10 −2 M ) and velocity 0.27c (0.15c) [4,16] (See however [17] for an alternative interpretation.) Similar results are obtained using more sophisticated 1D simulations of radiation transport along spherical shells of mass ejecta [5,6].…”
Section: Introductionsupporting
confidence: 81%
“…A fit of AT2017gfo light curves to a semianalytical two-components spherical model indicates a lanthanide poor (rich) blue (red) component of mass 2.5×10 −2 M (5.0×10 −2 M ) and velocity 0.27c (0.15c) [4,16] (See however [17] for an alternative interpretation.) Similar results are obtained using more sophisticated 1D simulations of radiation transport along spherical shells of mass ejecta [5,6].…”
Section: Introductionsupporting
confidence: 81%
“…Temperatures of the ejecta are evaluated with an equation of state (Blinnikov et al 1996), taking into account the energy generation through nuclear reactions (Rosswog et al 2017). The model has four parameters; the mass of the ejecta (Mej), the expansion velocity (vex), the electron fraction (Ye), and entropy per baryon (s), where Ye and s are evaluated when the temperature is equal to 9 × 10 9 K. We have performed calculations for parameters of Ye = 0.1, 0.15, 0.2, 0.25, and 0.3, and vex/c = 0.05, 0.1, and 0.2 with fixed parameters Mej = 0.03M⊙, which is comparable to masses adopted in kilonova models for GW170817 (Tanaka et al 2017;Kasen et al 2017), and s = 10kB, where kB is the Boltzmann constant. We investigate the following three cases; (a) the nine nuclei ( 121,123,125,127 Sn,128,129 Sb,129,131 Te, and 134 I) are assumed to be always stayed in their GSs: (b) the nine nuclei in their ISs with 100% β − BRs: and (c) the four nuclei, 123,125,127 Sn, and 128 Sb, whose IS largely dominates over its GS even when IS is not excited from GS (Appendix A), are assumed to be always stayed in their ISs with 100% β − BRs.…”
Section: Evolution Of Abundances and Energy Generation Rates Of Ejectamentioning
confidence: 99%
“…A gravitational wave source, GW170817, has been identified to be a neutron star merger (NSM) (Abbott et al 2017) and the association was observationally confirmed with a kilonova, AT2017gfo, whose light curve has been modeled with two components; early blue and later red ones (Cowperthwaite et al 2017;Tanaka et al 2017;Tanvir et al 2017;Kasen et al 2017;Villar et al 2017;Smartt et al 2017). In the scenario, the kilonova is possibly powered by the radioactive decay of neutron(n)-rich matter freshly synthesized in ejecta from NSM through r-process nucleosynthesis (Li & Paczyński 1998;Wanajo et al 2014).…”
Section: Introductionmentioning
confidence: 97%
“…As a comparison, the mass of the dynamical ejecta of double NS mergers is typically ∼10 −4 -10 −2 M e (Rosswog 2007;Bauswein et al 2013;Hotokezaka et al 2013a). It also does not conflict with the estimation of M ej ∼10 −3 -10 −2 M e for the dynamical ejecta of GW170817 (Abbott et al 2017d;Utsumi et al 2017;Tanaka et al 2017;Matsumoto et al 2018). In a few recent studies, a more precise ejecta mass of M ej ∼0.05M e was estimated when modeling the GW170817 kilonova (Cowperthwaite et al 2017;Drout et al 2017;Kasliwal et al 2017;Kasen et al 2017;Villar et al 2017;Waxman et al 2017).…”
Section: Numerical Resultsmentioning
confidence: 83%